2000
DOI: 10.1097/00002060-200009000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Motor Control Assessment for Rhizotomy in Cerebral Palsy

Abstract: PEMG patterns may allow the physician to select the appropriate children with spastic cerebral palsy to receive SPR with good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…32,33 The greatest benefit is seen in young children (3-7 years of age) with spastic diplegia but stable trunk control and good lower extremity strength.…”
Section: Ongoing Care In the Medical Homementioning
confidence: 99%
“…32,33 The greatest benefit is seen in young children (3-7 years of age) with spastic diplegia but stable trunk control and good lower extremity strength.…”
Section: Ongoing Care In the Medical Homementioning
confidence: 99%
“…25 Children with CP who had better gait patterns had increased stretch reflex of the calf muscles only 4 with equinus gait, 4,22 whereas those who had worse gait patterns had lower EMG activities or diffuse coactivation of the leg muscles 4,14 with more proximal joint involvement. 14,22 In this study, we found that reciprocal EMG activities are present in normal gait, whereas the cocontraction present in CP gait suggests an impairment of supraspinal control that results in the persistence of immature locomotor patterns such as equinus gait. A reciprocal model of leg muscle activation 6,26,27 with the mutual modulation of monosynaptic and polysynaptic responses 6,27 depends on the maturation of supraspinal motor centers.…”
Section: August 2003mentioning
confidence: 55%
“…12 However, SPR should not be used for such cases because it has a permanent effect and may increase existing weakness. 8,12,14 In the previous study, SPR did not improve or may even aggravate the function for these children with pattern V. 14 Serial casting, tendon lengthening, or tenotomy may be needed for children with CP who have muscle shortening or contracture to increase the ROM by lengthening either muscle or tendon, or both. 35 Tendon lengthening or tenotomy may be more beneficial in cases in which reduced extensibility results from inappropriate muscle length, whereas serial casting is more appropriate if muscle hyperactivity is present.…”
Section: August 2003mentioning
confidence: 83%
See 2 more Smart Citations